Stem section and planting method: its effect on Tithonia diversifolia biomass production - Gonz?lez, Daimarys; Ruiz, Tom?s El?as; D?az, Humberto (Cuban Journal of Agricultural Science, 2013)
The effect of the stem section, basal or middle, as well as the way of placing the stick (standing or lying) within the furrow in the biomass production of Tithonia diversifolia in both weather seasons. A design of random blocks in factorial arrangement (2 x 2), with four copies, was used. The results showed an interaction between the evaluated factors of height during the rainy and dry seasons (P < 0.05, P < 0.01), respectively. When planting the middle part of the stem, either standing or lying, the height obtained was higher. In the case of the growing, weight/leaf and leaves percentage indicators there was interaction among factors only during the dry season. Growing showed differences (P < 0.05) and it was worst when planting the lying basal part. On the contrary, the leaves percentage was inferior (P < 0.01) when planting the standing middle part. For the weight/leaf the best values were achieved when planting the lying middle part. The stem section influenced (P < 0.001) in the growing/d of the plant during the rainy period, as well as in the number of leaves/plants during the dry period. The middle part was superior for both indicators. This factor also influenced in the annual (P < 0.01) and seasonal (P < 0.05, rainy period and P < 0.001, dry period) yield. Superior values were obtained in all the cases for the middle section. There was a higher population of stems/ha (P < 0.01) when planting the middle section for the first year of evaluation. During the second year the population showed interaction (P < 0.05), and the lowest result was found when planting the standing middle part. It can be concluded that the Tithonia diversifolia should be planted, preferably, lying the stick in the bottom of the furrow using the middle section of the stem. Key words: Tithonia, plantation, biomass production